Aleksandr Vasilevich Viskovatov and his Istoricheskoe opisanie odezhdy i vooruzheniia rossiiskikh voisk. (1st October 2020) - Horbal, Bogdan
ABSTRACT: This article is devoted to Aleksandr Vasilevich Viskovatov's Istoricheskoe opisanie odezhdy i vooruzheniia rossiiskikh voisk [Historical description of the uniforms and arms of the Russian armies]. Published over the span of more than 20 years it encompasses 30 volumes of explanatory text and 30 volumes of illustrative materials (lithographs) dealing with the time period from the Middle Ages to the reign of Emperor Nicholas I (d. 1855). Unique in scope and size, this immense publication remains, even to this day, the most widely recognized, cited, and consulted work on the subject.